Colletotrichum fructicola Causal agent of Shot-Hole Symptoms on Leaves of Prunus sibirica in China - Han, Shan (Plant disease, 2023)
Prunus sibirica L. (Siberian apricot) is a member of the Rosaceae family and an ecologically important tree species in China (Buer et al., 2022). Shot hole symptoms on the leaves were observed in five Siberian apricot groves in Chengdu (103.81 E, 30.97 N), Sichuan province in July 2020. The symptoms first appeared as small purplish-brown spots with yellow rings around them. As the disease progressed, the damaged area (diameter 1.5-3.0 cm) became necrotic and fell off. The disease incidence was about 60% and the disease index was 28.6 of leaves in the grove. in most severe cases. Fifteen symptomatic leaves were collected from 5 different trees in an orchard. Pathogen isolation was performed from symptomatic leaf tissue (5 × 5 mm) though surface disinfection (in 70% ethanol and 2% NaClO) and incubation on Potato Dextrose Agar (PDA) at 28℃ for 3 days. Overall 10 isolates with similar colony morphology were obtained from the 15 infected tissue pieces, and three representative isolates (XCK 2-4) were selected for further study. Colonies of the isolates on PDA were initially cottony, pale white to grayish-green with abundant aerial hyphae and produced conidial masses after 7 days. Conidiogenous cells were clavate and aggregated in acervuli. Conidia were smooth-walled, single-celled, straight, and slightly obtusely rounded at both ends, 12.8 to 18.7 × 4.3 to 5.7 μm in size (Fig. 1). The morphological characteristics of the three isolates were consistent with the description of species in the Colletotrichum gloeosporioides complex. DNA was amplified using the following primers pairs for the internal transcribed spacer (ITS) region of rDNA and partial sequences of beta-tubulin (TUB2), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), chitin synthase (CHS-1), and translation elongation factor (TEF-1), respectively: ITS1/ITS4, T1/Bt2b, GDF/GDR, CHS-F/CHS-R, and EF-F/EF-R (Vieira et al., 2014). Accession numbers (MW228049, MW284974, MW284976, MW284975 and MW284977, respectively) were obtained afterepositing all the resulting sequences in GenBank. Nucleotide blast showed 99 to 100% identities with Colletotrichum fructicola (GenBank accessions nos. MZ961683, MW284974, MN525881, MN525860, MF627961). Phylogenetic analysis of combined ITS-TUB-GAPDH genes using the Mrbayes inference method showed that the three isolates clustered with three reference isolates of C. fructicola as a distinct clade (Fig. 2). To verify Koch's postulates, ten 3-year-old healthy potted plants of P. sibirica were inoculated by spraying a conidial suspension (6 × 105 conidia/mL) of isolate XCK2 on both sides of leaves, and the control leaves were sprayed with sterile water. Then, all treatments were placed in a moist environment (25±2°C, 80% relative humidity, natural light). The inoculated plants showed typical symptoms of plants with natural infections, while the controls remained asymptomatic after 14 days. The pathogen C. fructicola was re-isolated from all inoculated plants, and the culture and fungus characteristics were the same as those of the original isolate. Colletotrichum fructicola was not isolated from the control plants. The results indicated that C. fructicola is the causal agent of the disease. Colletotrichum fructicola was reported as a leaf pathogen on Camellia chrysantha in China (Zhao et al., 2021). This is the first report of C. fructicola causing P. sibirica leaf shot-hole in the world. The identification of C. fructicola could provide relevant information for applying management strategies and research on the Siberian apricot disease